Indonesian-British Strategic Partnership in the Perspective of International Treaty Law - Winsherly Tan; Neha Aswin Maysura (Universitas Muhammadiyah Purwokerto, 2023)
Countries must interact with other nations or international organizations in order to meet their diverse needs. Countries and countries, countries and international organizations, or one international organization and another international organization can all engage in international relations. One of the forms of international agreements carried out by a country is bilateral cooperation. Among the many countries that have cooperated with Indonesia, one of them is UK, a country that has had a long-standing partnership with Indonesia for approximately 70 years. The research method applied in this study is the normative legal research method. This method is used to describe how the law, particularly international agreements, perceives the bilateral partnership between Indonesia and UK. The ‘conceptual approach’ is chosen to provide insights into the analysis of the strategic partnership between Indonesia and UK. Additionally, various aspects and legal concepts underlying this partnership are analyzed in this research, including the Law Number 37 of 1999 regarding Foreign Relations and the Law Number 24 of 2000 regarding International Agreements. The results of the study show that the implementation of the cooperation agreement between Indonesia and the United Kingdom is in accordance with the two fundamental principles of international agreements according to Kartasasmita, the implementation of the agreement between Indonesia and England also fulfills several theories of the factors in the occurrence of international cooperation, including advances in technology; Economic progress and development; and There is awareness and willingness to negotiate.Keywords: International Agreement, Bilateral, Indonesia-UK